Inovasi Penjernihan Minyak Goreng Bekas dengan Alat Purification Oil - Desi Erlita; Amallia Puspitasari; Aditya Rizki Pratama (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Waste cooking oil produced by households and industries. The use of waste cooking oil be fuel, soap, floor cleaner, and candles have been developed. The use of waste cooking oil must be through purification step. A method of purification oil also have been developed, but the methods already there still managed to take optimal results. This research for development of previous studies, so results of this oil can be directly used to a different product with economic value. This research condist of 2 stages, treatment process and purification process. The treatment process using bentonite and potassium hydroxide (KOH). The purification process using purification oil instrument (capacity 5 liters) fitted with zeolite, filter paper and cotton a bandage. The purification of uses adsorption method for 24 hours. Purification process happened due to differences in weights molecules or porocity causeing some molecules bound stronger on the surface  of on the molecular. The use of KOH and bentonite to treatment process is very effective. While purification oil instrument can filer waste cooking oil that q brown and smelling become clear yellow, no longer smelling and the surface smooth. This research can decrease the free fatty acid  58% and peroxide 47,6%.